PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP CASHLESS TRANSACTION BEHAVIOR (STUDI PADA KARYAWAN SEKRETARIAT DAERAH KABUPATEN BLORA) - Wahyu Fitri Eka Muttasari; Fitri Lukiastuti (Magister Manajemen STIE Bank BPD Jateng, 2020)
The purpose of this study is to analyze the effect of financial literacy on cashless transaction behavior mediated by lifestyles on the employees of the Blora Regency Regional Secretariat. The population as well as the sample in this study amounted to 112 Civil Servants (PNS) Blora Regency Secretariat. Data were analyzed using the Partial Least Square (PLS) method and using the SmartPLS 3 tool. The sampling method is the saturated or census sampling method. Data collected by questionnaire. The results of this study are financial literacy has a significant positive effect on lifestyle variables, lifestyle has a positive and significant effect on cashless transaction behavior variables, financial literacy has a significant positive effect on cashless transaction behavior variables, and lifestyle is not related to financial literacy variables and variables cashless transaction behavior. Furthermore, the R-square value for the latent variable of cashless transaction behavior is 0.460, this means that the financial literacy variable increased by 46% of the cashless transaction behavior, and for the lifestyle latent variable by 0.402, meaning that financial literacy was 40.2% for the style life. While the rest is explained by other variables not included in this study.